KINERJA GURU PROFESIONAL DI TAMAN KANAK-KANAK SE-KOTA PONTIANAK - Morsek, Wita Kristina; Halida, Halida; Ali, Muhamad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to identify the performance of professional teachers of kindergartens in Pontianak City. This research is descriptive research with quantitative approach in the form of survey. The population of this study is all kindergarten teachers in Pontianak City who bersetifikasi. The number of samples used are 87 teachers, the kindergarten teachers who are already undergraduate (S1) and certified taken by cluster random sampling. The location of the research was conducted in 27 kindergartens spread in three sub-districts in Pontianak City, Pontianak Utara Subdistrict, South Pontianak Subdistrict and South Pontianak Subdistrict. Data collection techniques used closed questionnaires and documentation. Validity and reliability of data using Moment and Alpha Croncbach's Product Correlation techniques. Data from questionnaire were analyzed using quantitative analysis percentage. The results of this study indicate that the performance of professional teachers kindergarten in Pontianak city included into the category very well with the percentage reached 87.48%. Specifically, the results of this study indicate that 1) the performance of kindergarten teachers in planning in Pontianak including good category with percentage 86,96%, 2) the performance of kindergarten teachers in the implementation in Pontianak including excellent categorize with percentage 87,91% and 3) the performance of kindergarten teachers in the assessment of learning in the city of Pontianak including very good category with percentage,87,58%. Keywords: Performance, Professional Teacher, Kindergarten.Â